Návrh bezdrátové sítě pro SOŠ Podyjí - Truhlář, Petr (Vysoké učení technické v Brně. Fakulta podnikatelská, 2010)
Pro svoji práci jsem si vybral návrh bezdrátové sítě, která bude v praxi aplikována na SOŠ Podyjí. V této práci se budu zabývat výběrem vhodného standardu bezdrátové sítě a jeho využití. Teoretická část mé práce se bude zabývat problematikou bezdrátových sítí a jejich zabezpečení. V praktické části bude vybráno nejvhodnější řešení z uvedených standardů, zabezpečení a zařízení s ohledem na pořizovací cenu.

For my paper I have chosen project of a wireless network, which will be actually applied at SOS Podyji. In my paper I will deal with selection of a suitable concept of the wireless network and the functional use of the concept. In a theoretical part of my paper I will engage in wireless networks in general and in security of wireless networks. In a practical part of my paper I will select the most convenient solution, combining the chosen concept, security features and networking devices. I will select the networking devices with regard to their price.
Concept of Wireless Network for SOŠ Podyjí
Keywords: Wi-Fi; IEEE 802.11; LAN; WAN; WEP; WPA; WPA2; bezpečnost bezdrátových sítí; topologie sítí; UTP; STP; Wi-Fi; IEEE 802.11; LAN; WAN; WEP; WPA; WPA2; security of wireless networks; network topology; UTP; STP